Assessment of microplastics contamination in riverine environments: Urban stretch of Cauvery and Kollidam rivers of southern India - S. Venkatramanan; K. Radhakrishnan; R. Muthuramalingam; K. Sivakumar; T. Kongeswaran; K. Prabakaran; R. Rameshkumar; V. Madavaraj (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Enhancing CO2 capture capacity and selectivity in UTSA-16(Co) via elevated-temperature synthesis for flue gas separation - Ranjit Gaikwad; Sunita Gaikwad; Jiayi Li; Hiluf T. Fissaha; Radhakrishnan Anbarasan; Hua An; Le Xu; Shipeng Ding; Qiang Wang (Journal of Environmental Chemical Engineering, 2026)

Impact of coastal pollution on human health: A comparative study on biochemical profile and microbial diversity of coastal and non-coastal populations in Tamil Nadu, India - A. T. Rithi; Jayenth Jayachandran; Abhijit Mitra; Priyadarshini Shanmugam; Alice Peace; Divya Ilanchorian; Antara Banerjee; Arun Kumar Radhakrishnan (Journal of Coastal Conservation, 2026)

Assessment of urban spatial patterns and land use efficiency in Tiruchirappalli city, Tamil Nadu, India - T Alagu Venkatesh; Nisha Radhakrishnan (Advances in Space Research, 2026)

Phytomolecule-doped green synthesis of Ag@Fe bimetallic nanocomposites from Abutilon indicum leaf extract: Antimicrobial activity against Mycobacterium spp. and pathogenic bacteria and their cytotoxicity assessment in zebrafish embryos - Mary Shamya Arokiarajan; J. John Christopher; S. Ranjani; S.A. Wasim Akram; K.M. Ramkumar; S. Tirumala Santoshkumar; Noman Anwar; T. Rajaseker; M Radhakrishnan; V. Muzammil Ahmed; Murali Krishna Prasad; K. Kabiruddin Ahmed; et al. (Biocatalysis and Agricultural Biotechnology, 2025)

Microsatellite-Based Genetic Diversity, Population Structure and Bottleneck Analysis in Peanut: Conservation and Utilization Implications - Chandramohan Sangh; Janki BharatBhai Pandya; Vora Zarna; Radhakrishnan T; S. K. Bera (Plant Molecular Biology Reporter, 2025)

Bacillus licheniformis and commercial fungicides exhibit high potential against major pathogens inciting grain discolouration disease in rice, Oryza sativa L. - P. K. Amrith; M. Surendran; N. V. Radhakrishnan; Susha S. Thara; T. Anuradha; B. Ajay (Indian Phytopathology, 2025)

Whole genome sequencing based prediction of antimicrobial resistance evolution among the predominant bacterial pathogens of diabetic foot ulcer - Vipina Vinod T. N.; Manjusha Premnath; Jos V. Stanley; Nimmy Paul; Jyothis Mathew; E. K. Radhakrishnan (World Journal of Microbiology and Biotechnology, 2025)

Bioactive Metabolites of Serratia sp. NhPB1 Isolated from Pitcher of Nepenthes and its Application to Control Pythium aphanidermatum - Aswani Ravi; Soumya Das; Sebastian Korattiparambil Sebastian; Charuvila T. Aravindakumar; Jyothis Mathew; Radhakrishnan Edayileveettil Krishnankutty (Probiotics and Antimicrobial Proteins, 2025)

A concise review of the impact of groundwater pollution in coastal regions on human gut microbiome composition and its effect on human health - Rithi A T; Antara Banerjee; Abhijit Mitra; Keerthi Nethaji; Divya Ilanchoorian; Arun Kumar Radhakrishnan (Groundwater for Sustainable Development, 2024)

Diversity of complex polysaccharide degrading bacteria from the sediments of interlinked high Arctic fjords, Svalbard - Vishnupriya S.; Jabir T.; Adarsh B.M.; Hafsa Kattatheyil; Shahana Kabeer S.; Krishnan K.P.; Radhakrishnan C.K.; Mohamed Hatha A.A. (Regional Studies in Marine Science, 2023)

First report of bacterial wilt of yardlong bean (Vigna unguiculata subsp. sesquipedalis (L.) Verdc.) caused by Kosakonia oryzae in India - Talla Sushmitha; Abdulmajeed Sajeena; Deepu Mathew; Joy Michal Johnson; Nanjil Venkatachalam Radhakrishnan; Jacob John; T. Anuradha (Journal of Plant Pathology, 2023)

Non-thermal technologies: Solution for hazardous pesticides reduction in fruits and vegetables - Ranjitha Gracy T. K.; Sharanyakanth P. S.; Mahendran Radhakrishnan (Critical Reviews in Food Science and Nutrition, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Anti-inflammatory effect and mechanism of action of ellagic acid-3,3′,4-trimethoxy-4′- O -α-L-rhamnopyranoside isolated from Hopea parviflora in lipopolysaccharide-stimulated RAW 264.7 macrophages - B. Prabha; S. Sini; T. S. Priyadarshini; P. Sasikumar; Greeshma Gopalan; Jayesh P. Joseph; M. M. Jithin; V. V. Sivan; P. Jayamurthy; K. V. Radhakrishnan (Natural Product Research, 2021)

Impact of Supplements on Enhanced Activity of Bacillus amyloliquefaciens BmB1 Against Pythium aphanidermatum Through Lipopeptide Modulation - Aswani Ravi; Sukanya Rajan; Nejumal Kannankeril Khalid; Midhun Sebastian Jose; Charuvila T. Aravindakumar; Radhakrishnan Edayileveettil Krishnankutty (Probiotics and Antimicrobial Proteins, 2021)

Promalabaricone B from Myristica fatua Houtt. seeds demonstrate antidiabetic potential by modulating glucose uptake via the upregulation of AMPK in L6 myotubes - B. Prabha; S. Sini; D. R. Sherin; S. Neethu; K. B. Rameshkumar; T. K. Manojkumar; P. Jayamurthy; K. V. Radhakrishnan (Natural Product Research, 2021)

Fatty acid desaturase-2 (ahFAD2) mutant alleles in peanut (Arachis hypogaea L.) pre-breeding lines: an insight into the source, features, discourse, and selection of novel pre-breeding lines - J. H. Kamdar; M. D. Jasani; B. C. Ajay; Kirti Rani; N. Manivannan; R. P. Vasanthi; K. L. Dobariya; M. K. Pandey; P. Janila; T. Radhakrishnan; R. K. Varshney; S. K. Bera (Genetic Resources and Crop Evolution, 2021)

G × E interactions in QTL introgression lines of Spanish-type groundnut (Arachis hypogaea L.) - A. L. Rathnakumar; Surendra S. Manohar; Hajisaheb L. Nadaf; Sudam C. Patil; Milind P. Deshmukh; P. P. Thirumalaisamy; Narendra Kumar; H. B. Lalwani; P. Nagaraju; Basavaraj Yenagi; S. S. Patil; J. Suryawanshi; et al. (Euphytica, 2020)

Correction to: Common Methodology for Cardiac and Ocular Artifact Suppression from EEG Recordings by Combining Ensemble Empirical Mode Decomposition with Regression Approach - Rajesh Patel; K. Gireesan; S. Sengottuvel; M. P. Janawadkar; T. S. Radhakrishnan (Journal of Medical and Biological Engineering, 2020)

Chemical and biological studies on Bridelia ferruginea grown in Nigeria - Michael Afolayan; Radhakrishnan Srivedavyasasri; Olayinka T. Asekun; Oluwole B. Familoni; Samir A. Ross (Natural Product Research, 2019)

Phytochemical study of Piliostigma thonningii, a medicinal plant grown in Nigeria - Michael Afolayan; Radhakrishnan Srivedavyasasri; Olayinka T. Asekun; Oluwole B. Familoni; Abayomi Orishadipe; Fazila Zulfiqar; Mohamed A. Ibrahim; Samir A Ross (Medicinal Chemistry Research, 2018)

Dietary Supplement of Medicinal Herbal Leaf Powder on Growth Performance, Digestive Enzymes Activities, Energy Utilization and Vitamin Levels of the Freshwater Prawn Macrobrachium rosenbergii - T. Muralisankar; P. Saravana Bhavan; S. Radhakrishnan; P. Santhanam (Proceedings of the Zoological Society, 2018)

Improving oil quality by altering levels of fatty acids through marker-assisted selection of ahfad2 alleles in peanut (Arachis hypogaea L.) - Sandip K. Bera; Jignesh H. Kamdar; Swati V. Kasundra; Pitabas Dash; Anil K. Maurya; Mital D. Jasani; Ajay B. Chandrashekar; N. Manivannan; R. P. Vasanthi; K. L. Dobariya; Manish K. Pandey; Pasupuleti Janila; et al. (Euphytica, 2018)

Suppression of Baseline Wander Artifact in Magnetocardiogram Using Breathing Sensor - Rajesh Patel; K. Gireesan; S. Sengottuvel; M. P. Janawadkar; T. S. Radhakrishnan (Journal of Medical and Biological Engineering, 2017)

Common Methodology for Cardiac and Ocular Artifact Suppression from EEG Recordings by Combining Ensemble Empirical Mode Decomposition with Regression Approach - Rajesh Patel; K. Gireesan; S. Sengottuvel; M. P. Janawadkar; T. S. Radhakrishnan (Journal of Medical and Biological Engineering, 2017)
Electroencephalography (EEG) is a non-invasive way of recording brain activities, making it useful for diagnosing various neurological disorders. However, artifact signals associated with eye blinks or the heart spread across the scalp, contaminating EEG recordings and making EEG data analysis difficult. To solve this problem, we implement a common methodology to suppress both cardiac and ocular artifact signal, by correlating the measured contaminated EEG signals with the clean reference electro-oculography (EOG) and electrocardiography (EKG) data and subtracting the scaled EOG and EKG from the contaminated EEG recording. In the proposed methodology, the clean EOG and EKG signals are extracted by subjecting the raw reference time-series data to ensemble empirical mode decomposition to obtain the intrinsic mode functions. Then, an unsupervised technique is used to capture the artifact components. We compare the distortion introduced into the brain signal after artifact suppression using the proposed method with those obtained using conventional regression alone and with a wavelet-based approach. The results show that the proposed method outperforms the other techniques, with an additional advantage of being a common methodology for the suppression of two types of artifact.

Effects of Probiotics on Survival, Growth and Digestive Enzymes Activities in Freshwater Prawn Macrobrachium rosenbergii (De Man 1879) - C. Seenivasan; S. Radhakrishnan; T. Muralisankar; P. Saravana Bhavan (Proceedings of the Zoological Society, 2016)

Influence of Probiotics on Survival, Growth, Biochemical Changes and Energy Utilization Performance of Macrobrachium rosenbergii Post-larvae - C. Seenivasan; S. Radhakrishnan; R. Shanthi; T. Muralisankar; P. Saravana Bhavan (Proceedings of the Zoological Society, 2015)

Marker-assisted introgression of a QTL region to improve rust resistance in three elite and popular varieties of peanut (Arachis hypogaea L.) - Rajeev K. Varshney; Manish K. Pandey; Pasupuleti Janila; Shyam N. Nigam; Harikishan Sudini; M. V. C. Gowda; Manda Sriswathi; T. Radhakrishnan; Surendra S. Manohar; Patne Nagesh (Theoretical and Applied Genetics, 2014)

UV-Visible Photoluminescence of TiO2 Nanoparticles Prepared by Hydrothermal Method - S. Mathew; Amit kumar Prasad; Thomas Benoy; P. P. Rakesh; Misha Hari; T. M Libish; P. Radhakrishnan; V. P. N. Nampoori; C. P. G. Vallabhan (Journal of Fluorescence, 2012)

Identification of hot spots and well managed areas of Pichavaram mangrove using Landsat TM and Resourcesat—1 LISS IV: an example of coastal resource conservation along Tamil Nadu Coast, India - T. Srinivasa Kumar; R. S. Mahendra; Shailesh Nayak; K. Radhakrishnan; Kali C. Sahu (Journal of Coastal Conservation, 2012)

Identification of several small main-effect QTLs and a large number of epistatic QTLs for drought tolerance related traits in groundnut (Arachis hypogaea L.) - K. Ravi; V. Vadez; S. Isobe; R. R. Mir; Y. Guo; S. N. Nigam; M. V. C. Gowda; T. Radhakrishnan; D. J. Bertioli; S. J. Knapp; R. K. Varshney (Theoretical and Applied Genetics, 2011)

Thermodynamics of chromium(III) adsorption onto a cation exchanger derived from saw dust of Jack wood - T. S. Anirudhan; P. G. Radhakrishnan (Environmental Chemistry Letters, 2011)

Comparative study of interspecific genetic divergence and phylogenic analysis of genus Jatropha by RAPD and AFLP - D. V. N. Sudheer Pamidiamarri; Nirali Pandya; Muppala P. Reddy; T. Radhakrishnan (Molecular Biology Reports, 2009)

Analysis of diallel cross for some physical-quality traits in peanut (Arachis hypogaea L.) - K. Hariprasanna; Chuni Lal; T. Radhakrishnan; H. K. Gor; B. M. Chikani (Euphytica, 2008)

Characterization of a Pseudomonas fluorescens strain from tomato rhizosphere and its use for integrated management of tomato damping-off - Jayaraman Jayaraj; T. Parthasarathi; N. V. Radhakrishnan (BioControl, 2007)

Catalase: A repertoire of unusual features - Prashen Chelikani; T. Ramana; T. M. Radhakrishnan (Indian Journal of Clinical Biochemistry, 2005)

Zone-Specific Micromechanical Properties of the Extracellular Matrices of Growth Plate Cartilage - Priya Radhakrishnan; Naama T. Lewis; Jeremy J. Mao (Annals of Biomedical Engineering, 2004)

Enteromorpha compressa (L.) Greville an edible green alga as a source of antiallergic principle (S) - B. Venkata Raman; D. N. Rao; T. M. Radhakrishnan (Indian Journal of Clinical Biochemistry, 2004)